Mexico : Selected Issues. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2015)
This Selected Issues paper analyzes fiscal multipliers in Mexico. Estimates of fiscal multipliers--obtained from state-level spending--fall within 0.6-0.7 after accounting for dynamic effects. However, the size of multipliers varies with the output gap. The planned fiscal consolidation-under the estimated multipliers-is projected to subtract on average 0.5 percentage points from growth over 2015-20. However, there are offsetting effects. The positive growth impulse of lower costs on manufactured goods production is estimated to reach 0.5 percentage point in 2015 and 2016, largely offsetting the impact of fiscal consolidation on growth in the near term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet